Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
ta có \(\hept{\begin{cases}\left(\frac{1}{2}x-5\right)^{20}\ge0\forall x\\\left(y^2-\frac{1}{4}\right)^{10}\ge0\forall y\end{cases}\Rightarrow\hept{\begin{cases}\frac{1}{2}x-5=0\\y^2-\frac{1}{4}=0\end{cases}\Leftrightarrow}\hept{\begin{cases}\frac{1}{2}x=5\\y^2=\frac{1}{4}\end{cases}\Leftrightarrow\hept{\begin{cases}x=10\\y=\pm\frac{1}{2}\end{cases}}}}\)
Bài làm:
Ta có: \(\hept{\begin{cases}\left(\frac{1}{2}x-5\right)^{20}\ge0\left(\forall x\right)\\\left(y^2-\frac{1}{4}\right)^{10}\ge0\left(\forall y\right)\end{cases}\Rightarrow\left(\frac{1}{2}x-5\right)^{20}+\left(y^2-\frac{1}{4}\right)^{10}\ge0\left(\forall x,y\right)}\)
Mà theo đề bài: \(\left(\frac{1}{2}x-5\right)^{20}+\left(y^2-\frac{1}{4}\right)^{10}\le0\)
\(\Rightarrow\hept{\begin{cases}\left(\frac{1}{2}x-5\right)^{20}=0\\\left(y^2-\frac{1}{4}\right)^{10}=0\end{cases}}\Rightarrow\hept{\begin{cases}x=10\\y=\pm\frac{1}{2}\end{cases}}\)
[2x-5]^2016+[3y+4]^2014<hoặc=0
=>2x-5=0 và 3y+4=0 (vì [2x-5]^2016+[3y+4]^2014>hoặc=0 với mọi x;y)
=>x=5/2 và y=-4/3
vậy x=5/2 và y=-4/3
Ta có :
\(\begin{cases}\left(\frac{1}{2x}-5\right)^{20}\ge0\\\left(y^2-\frac{1}{4}\right)^{10}\ge0\end{cases}\)
Mà : \(\left(\frac{1}{2x}-5\right)^{20}+\left(y^2-\frac{1}{4}\right)^{10}\le0\)
\(\Rightarrow\begin{cases}\left(\frac{1}{2x}-5\right)^{20}=0\\\left(y^2-\frac{1}{4}\right)^{10}=0\end{cases}\)
(+) \(\frac{1}{2x}-5=0\)
\(\Rightarrow x=\frac{1}{10}\)
(+) \(y^2-\frac{1}{4}=0\)
\(\Rightarrow\left[\begin{array}{nghiempt}y=\frac{1}{2}\\y=-\frac{1}{2}\end{array}\right.\)
Vậy \(\left(x;y\right)\in\left\{\left(\frac{1}{10};\frac{1}{2}\right);\left(\frac{1}{10};-\frac{1}{2}\right)\right\}\)
Do \(\left(\frac{1}{2}x-5\right)^{20}\ge0;\left(y^2-\frac{1}{4}\right)^{10}\ge0\)
=> \(\left(\frac{1}{2}x-5\right)^{20}+\left(y^2-\frac{1}{4}\right)^{10}\ge0\)
Mà theo đề bài: \(\left(\frac{1}{2}x-5\right)^{20}+\left(y^2-\frac{1}{4}\right)^{10}\le0\)
=> \(\left(\frac{1}{2}x-5\right)^{20}+\left(y^2-\frac{1}{4}\right)^{10}=0\)
=> \(\begin{cases}\left(\frac{1}{2}x-5\right)^{20}=0\\\left(y^2-\frac{1}{4}\right)^{10}=0\end{cases}\)=> \(\begin{cases}\frac{1}{2}x-5=0\\y^2-\frac{1}{4}=0\end{cases}\)=> \(\begin{cases}\frac{1}{2}x=5\\y^2=\frac{1}{4}\end{cases}\)=> \(\begin{cases}x=10\\y\in\left\{\frac{1}{2};\frac{-1}{2}\right\}\end{cases}\)